Effect analysis of cracked thick plate on the stability by XFEM - Nguyễn Ngọc Thắng (Journal of Technical Education Science, 2017)
In this paper, effective analysis of cracked thick plate on the stability is studied with the extended finite element method (XFEM). Depending on its thickness, the plate may have various instability, especially when crevices occur. This effect is revealed by the critical buckling factor of plates subjected to compressing loads . The buckling load factor of cracked plates is obtained from the Matlab-based computing program using XFEM to build in quadrilateral iso-parametric element. The XFEM is widely used in many fields and common problems with cracking texture. Based on FEM but the XFEM improves by adding intermittent extension functions and approximation in the finite element to calculate the presence of crevices. The results are compared with previous studies to confirm the advantages and accuracy of the new method.